Management of complications in ophthalmic surgery - Boyd, Samuel; Wu, Lihteh; Mejia, Kayra; Duran, Laura; Chandeck, Eduardo (Panamá : Jaypee-Highligts Medical Publishers, 2009)
La cirugía oftámica se ha vuelto extremadamente sofisticada en los últimos años. Los cirujanos oculares fueron los primeros en introducir la microcirugía y el láser entre 1950 y los delicados instrumentos quirúrgicos y suturas.
Ophthamic surgery has become extremely sophisticated in the last yeras. Ocular surgeons where the first to introduce microsurgery and laser between the 1950 followed by delicate surgical instruments and sutures.
CONTENTS Chapter 1: Complications associated with local ophthalmic anesthesia techniques Chapter 2: Complications in Lasik Chapter 3: Phakic Anterior Chamber intraocular lenses Chapter 4: Complications of Phakic Posterior Chamber IOL's Chapter 5: Common Complications during phacoemulsification and others more...
Incluye índice
Keywords: CATARATAS (OFTALMOLOGIA); CATARACT -- SURGERY; ENFERMEDADES DE LOS OJOS